Utilização do método de Rietveld no estudo estrutural dos compostos K2MoXW(1-x)O4 - Ademir Antonio Guarnieri (2005)
The mixed compounds K2MoxW(1-x)O4 have been studied from the structural and phase transitions point of view. Differential Scanning Calorimetry experiments was used in order to determine the phase transition temperatures for two observed transitions above room temperature, for compounds with x = 0; 0.2; 0.4; 0.5; 0.6; 0.8 and 1 have been analysed. At room temperature, powder samples with these compositions have been studied by X-ray diffraction in a conventional Bragg- Brentano; lattice parameters and atomic coordinates were refined employing the Rietveld method. For the x = 0.5 compound, X-ray diffraction data have been collected in temperatures above room and Rieteveld refinements have been performed for the phases detected above each one of the two transitions. A curious fact, not reported in the literature for the pure compounds (x = 0 and x = 1), was observed in this compound - K2Mo0,5W0,5O4 - when new data were collected near room temperature, after a long period of time at high temperatures: the compound did not present the expected phase except after exposition to room atmosphere. A model for the crystal structure in this new phase is proposed. Intending to study their intermediate phase, referred in the literature for the pure compounds as modulated, experiments were performed using synchrotron radiation for obtaining high quality data allowing refining the modulation wave vector values, after the satellite reflections. Previous to all the above described research, a series of preliminary experiments involving three other compounds, which present modulated phases, - Rb2ZnCl4, AuTe2 and Rb2Cd2(SO4)3 - were performed in the stages of implementation of data collections and data analysis.